Penerapan Analisis Permintaan dan Elastisitas Harga untuk Pengembangan Produk UMKM Teras Steak - Etty Zuliawati Zed; Priyo Handoko; M. Abdul Rohman Rifki Aftoni; Dede Wijaya (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
The Micro, Small, and Medium Enterprises (MSME) industry, such as Teras Steak, plays a significant role in strengthening the economy. The purpose of this study is to evaluate how price influences demand and to calculate price elasticity as a foundation for business decision-making. The methodology employed includes sales data analysis, customer satisfaction surveys, and interviews. The findings indicate that demand for Teras Steak’s products is highly sensitive, meaning that price changes have a significant impact on the quantity demanded. Therefore, pricing strategies must consider a balance between sales volume and profit. To enhance competitiveness and maintain customer loyalty, it is recommended to diversify products, innovate the menu, adjust prices according to market segments, and implement effective promotions. Understanding this elasticity is crucial to support sustainable business growth.